The market for used cars: A new test of the lemons model - Winand Emons; George Sheldon (Hamburg Institute of International Economics (HWWA), 2002)
The lemons model assumes that owners of used cars have an informational advantage over potential buyers with respect to the quality of their vehicles. Owners of bad cars will try to sell them to unsuspecting buyers while owners of good cars will hold on to theirs. Consequently, the quality of traded automobiles should be sub-average. In contrast to previous work, the following paper tests both the assumption of informational asymmetry and the prediction of sub-average traded car quality using a sample consisting of all 1985 cars registered in the Swiss canton of Basle-City over the period 1985-1991. Our data support both the assumption and the prediction of the lemons model. The lemons problem does not appear to be widespread, however. – – Das "Lemons"-Modell unterstellt, dass die Verkäufer von gebrauchten Automobilen einen Informationsvorsprung gegenüber potenziellen Käufern haben. Die Besitzer von minderwertigen Automobilen werden versuchen, diese an unwissende interessierte zu verkaufen, während die Besitzer von hochrangigen Fahrzeugen diese eher behalten werden. Deshalb sollte die Qualität von gehandelten gebrauchten Automobilen unterdurchschnittlich niedrig sein. Im Gegensatz zu früheren Untersuchungen untersucht das vorliegende Papier die Annahme der Informationsasymmetrie und die Vorhersage der unterdurchschnittlichen Qualität von gehandelten Automobilen an Hand eines Datensatzes, der alle registrierten Automobile im Schweizer Kanton Basel-Stadt im Zeitraum 1985-1991 umfasst. Unsere Untersuchung bestätigt sowohl Annahme wie Vorhersage des "Lemons"-Modells, findet allerdings auch, dass das "Lemons"-Problem nicht weit verbreitet ist.
Keywords: L62; L15; D82; C41; 330; Adverse Selection; Used Car Market; Duration Models; Gebrauchtfahrzeug; Gebrauchtfahrzeughandel; Asymmetrische Information; Adverse Selection; Schätzung; Schweiz